<span>Solve this equation by completing the square. 3x^2 - 4x = -2 </span>Step 1: Divide by the leading coefficient (coef. of x^2), and transpose. (3x^2 - 4x)/3 = -2/3 x^2-2(2/3)x = -2/3 Complete the square, (x-2/3)^2 - 4/9 = -2/3 Solve for (x-2/3) (x-2/3)^2= -2/3 + 4/9 = -2/9 x-2/3 = ± (√2)i/3 Solve for x x=2/3± (√2)i/3 or x=(2±(√2)i)/3
When you expand the equation in the bracket you'll find out that you'll get a^6 + 4a^4 + !6a^2 - 4a^4 - 16a^2 -64. then your final result will be a^6 - 64 <span />